RAINIS’ APOLOGY OF THE ‘BASIC CLASS’: THE WORLD REVOLUTION OR THE NATIONAL EMANCIPATION? - Grumolte, Inese (Baltic Journal of Political Science, 2013)
The aim of this article is to analyze the reasons for Rainis’ appreciation of the phenomenon he labels as the ‘basic class’. The Latvian writer attributes this concept to the members of society who provide the livelihood for themselves by doing mainly the manual labour. Although thus a praise for the proletariat is voiced, the reasons are more nuanced than the common Soviet interpretation allowed to see. Rainis sees the ‘Basic class’ as a crucial agent in the struggle for Latvian national emancipation. At the same time, the article seeks an answer to the question why, according to Rainis, bourgeoisie is reluctant to fight this struggle.